2005
DOI: 10.1105/tpc.105.037341
|View full text |Cite
|
Sign up to set email alerts
|

Polar Localizing Class V Myosin Chitin Synthases Are Essential during Early Plant Infection in the Plant Pathogenic FungusUstilago maydis

Abstract: Fungal chitin synthases (CHSs) form fibers of the cell wall and are crucial for substrate invasion and pathogenicity. Filamentous fungi contain up to 10 CHSs, which might reflect redundant functions or the complex biology of these fungi. Here, we investigate the complete repertoire of eight CHSs in the dimorphic plant pathogen Ustilago maydis. We demonstrate that all CHSs are expressed in yeast cells and hyphae. Green fluorescent protein (GFP) fusions to all CHSs localize to septa, whereas Chs5-GFP, Chs6-GFP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
154
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(169 citation statements)
references
References 71 publications
12
154
2
1
Order By: Relevance
“…, 2015; Sanchez‐Leon et al . , 2011; Takeshita, Yamashita, Ohta, & Horiuchi, 2006; Weber, Assmann, Thines, & Steinberg, 2006). We hypothesized that Cda4:mCherry may therefore colocalize with a chitin synthase, which would provide a valuable insight into possible coordinated transport of these proteins and the mechanism of chitin deacetylation.…”
Section: Resultsmentioning
confidence: 99%
“…, 2015; Sanchez‐Leon et al . , 2011; Takeshita, Yamashita, Ohta, & Horiuchi, 2006; Weber, Assmann, Thines, & Steinberg, 2006). We hypothesized that Cda4:mCherry may therefore colocalize with a chitin synthase, which would provide a valuable insight into possible coordinated transport of these proteins and the mechanism of chitin deacetylation.…”
Section: Resultsmentioning
confidence: 99%
“…Myosin CHSs may play a role in a secretion pathway that is essential for the virulence of fungal pathogens. In U. maydis and Fusarium oxysporum, myosin CHSs are critically involved in (and required for) polarized growth during plant infection ( Weber et al, 2006 andMartín-Urdíroz et al, 2008). In U. maydis, it has been suggested that the Myosin Motor Domain (MMD) of ChsV supports exocytosis but not the long-range delivery of transport vesicles ( Treitschke et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…and Septoria sp. cultured in increased concentrations of fungicides are lower than the growth rate of the wild type [10]- [12].…”
Section: Introductionmentioning
confidence: 99%